2019
DOI: 10.1093/rpd/ncz270
|View full text |Cite
|
Sign up to set email alerts
|

Tritium Analysis in Urine by the Triple-to-Double Coincidence Ratio Method With the Hidex 300 Sl Liquid Scintillation Counter

Abstract: The triple-to-double coincidence ratio (TDCR) method is a liquid scintillation primary method for the absolute activity measurement of pure β− and pure electron capture emitters. This method requires specific three-photomultiplier liquid scintillation counters. The aim of the present work is to assess the TDCR method performance for routine tritium analysis in urine using an HIDEX 300 SL, the only three-photomultiplier liquid scintillation counter designed for routine laboratories. The physical parameters and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…There are many quenching indicators depending on the manufacturer of the LSC analyzer, but they all rely on the analysis of the pulse-height spectrum of the sample acquired with an external gamma source. A recent study 15 has shown that the TDCR value can also be used as a quench indicating parameter. Here we present results of TDCR measurements of H and Fe in Ultima Gold cocktail with efficiency variation performed by means of grey filters.…”
Section: Resultsmentioning
confidence: 99%
“…There are many quenching indicators depending on the manufacturer of the LSC analyzer, but they all rely on the analysis of the pulse-height spectrum of the sample acquired with an external gamma source. A recent study 15 has shown that the TDCR value can also be used as a quench indicating parameter. Here we present results of TDCR measurements of H and Fe in Ultima Gold cocktail with efficiency variation performed by means of grey filters.…”
Section: Resultsmentioning
confidence: 99%